Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing 2015
DOI: 10.18653/v1/d15-1309
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Domestic Abuse Discourse on Reddit

Abstract: Domestic abuse affects people of every race, class, age, and nation. There is significant research on the prevalence and effects of domestic abuse; however, such research typically involves population-based surveys that have high financial costs. This work provides a qualitative analysis of domestic abuse using data collected from the social and news-aggregation website reddit.com. We develop classifiers to detect submissions discussing domestic abuse, achieving accuracies of up to 92%, a substantial error red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 13 publications
2
55
0
1
Order By: Relevance
“…Analyzing personal sexual harassment stories from online social forums is fairly unexplored, to the best of our knowledge. However, recent works in a similar vein include detecting the presence of domestic abuse stories on social media sites (Schrading et al, 2015a;Schrading, 2015;Schrading et al, 2015b). In more distantly related work, NLP has been used for various sociallydriven tasks, such as detecting the presence of cyberbullying or incivility (Ziegele et al, 2018;Founta et al, 2018;Chen et al, 2012;Zhao et al, 2016;Agrawal and Awekar, 2018;Van Hee et al, 2018), and detecting and providing aid for signs of depression or suicidal thoughts (Pestian et al, 2010;Yazdavar et al, 2017;Stepanov et al, 2017;Fitzpatrick et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Analyzing personal sexual harassment stories from online social forums is fairly unexplored, to the best of our knowledge. However, recent works in a similar vein include detecting the presence of domestic abuse stories on social media sites (Schrading et al, 2015a;Schrading, 2015;Schrading et al, 2015b). In more distantly related work, NLP has been used for various sociallydriven tasks, such as detecting the presence of cyberbullying or incivility (Ziegele et al, 2018;Founta et al, 2018;Chen et al, 2012;Zhao et al, 2016;Agrawal and Awekar, 2018;Van Hee et al, 2018), and detecting and providing aid for signs of depression or suicidal thoughts (Pestian et al, 2010;Yazdavar et al, 2017;Stepanov et al, 2017;Fitzpatrick et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…De Choudhury and De (2014) studied mental health discourse and concluded that Reddit users openly share their experiences and challenges with mental illnesses in their personal and professional lives. Schrading et al (2015) studied domestic abuse and found that abuse-related discussion groups have more tightknit communities, longer posts and comments, and less discourse than non-abusive groups. Wallace et al (2014) tackled irony detection and concluded that Reddit provides a lot of context, which can help in dealing with the ambiguous cases.…”
Section: Background and Related Workmentioning
confidence: 99%
“…It divides violence into physical, sexual, psychological, and deprivational/neglect categories. The Duluth model provides another established categorization of types of violence, but was originally developed for therapy treating men who abuse women, rather than for understanding IPV scientifically (Rizza, 2009 Schrading et al (2015a) developed classifiers to determine whether a Reddit post described abuse. In the study, the subreddit to which the post belonged was used to map to binary gold-standard labels: if a post came from a subreddit such as /r/survivorsofabuse, it was categorized as a post about abuse.…”
Section: Background and Related Workmentioning
confidence: 99%